Incidence and Predictors of Angiographic Vasospasm, Symptomatic Vasospasm and Cerebral Infarction in Chinese Patients with Aneurysmal Subarachnoid Hemorrhage - Mijiti, Maimaitili (PLoS One, 2016)
INTRODUCTION: Cerebral vasospasm (CVS) is the most common neurological complication after aneurysmal subarachnoid hemorrhage (aSAH) and associated with poor functional outcome and mortality. Reports on incidence and predictors of CVS in Chinese patients with aSAH were scarce. We aimed to estimate the incidence and predictors of angiographic vasospasm (AV), symptomatic vasospasm (SV), and cerebral infarction in Chinese patients with aSAH. METHODS: We retrospectively reviewed the medical records of 542 consecutive aSAH patients admitted to neurosurgery department of the First Affiliated Hospital of Xinjiang Medical University in Urumqi city of China between January 1, 2011 and December 31, 2015. AV, SV and cerebral infarction were defined based on clinical data and neuroimaging findings. Univariate and multivariate analyses were performed to identify predictors of AV, SV or cerebral infarction. RESULTS: 343 (63.3%) patients fulfilled the inclusion and exclusion criteria. Of them, 182(53.1%) developed AV, 99 (28.9%) developed SV, and 87 (25.4%) developed cerebral infarction. A history of hypertension, poor modified Fisher grade (3–4) and poor Hunt-Hess grade (4–5) on admission were common risk factors for AV, SV and cerebral infarction. Patients from Uyghur ethnic group or other minorities were less likely to develop AV, SV or cerebral infarction, compared to those from Han ethic group after adjustment of other potential confounders. Additionally, age ≥53 years, leukocyte count ≥11× 10(9)/L on admission and being current or former smokers were independent risk factors of cerebral infarction. Leukocyte count ≥11× 10(9)/L on admission and aneurysm size ≥ 10 mm were independent risk factors of SV. Serum glucose level ≥7.0 mmol/L on admission was an independent risk factor of AV. CONCLUSION: Risk factors of different definitions of CVS were diverse in Chinese patients with aSAH; however, risk factors of SV and cerebral infarction seem to be similar. We recommend early and aggressive therapy in these patients at-risk of CVS.